A biorational approach for management of key plant pathogens - ARORA, SUMITRA; MOGHA, NAVIN KUMAR; BHARDWAJ, TULSI; SAHU, VIKRANT; DUBEY, SUNIL CHANDRA (The Indian Journal of Agricultural Sciences, 2015)
The antifungal potential of solvent extracts of four plants, viz. Polyalthia longifolia (Sonn.) Thw. (PL), Paederia foetida (PF), Limonia acidissima L. (LA) and Balanites aegyptiaca (L.) Del. (BA), were screened during the year 2010 and 2011 against important plant pathogenic fungi. The methanol, petroleum ether, chloroform and waterÂ  extracts, of the plants were bio-assayed against test fungi, Rhizoctonia bataticola, R. solani, Sclerotinia sclerotiorum, S. rolfsii, Fusarium oxysporum, Alternaria alternata and Pythium aphanidermatum. Out of 16 plant extracts, extracts of P. longifolia recorded significant antifungal activity (up to 84% inhibition) against almost all test fungi. The methanol extract of P. longifolia gave most promising results for inhibiting the test fungi, resulting in inhibition concentration (IC50) in the range of 200-600 ppm. Hence, a single methanol extract of the plant P. longifolia could act as a promising biofungicide for inhibiting the growth of different fungi responsible for crop losses. Thus these plants extracts have potential to act as effective fungicide.